ANALISIS PASAR BERSANGKUTAN DALAM PUTUSAN KPPU (STUDI PUTUSAN PERKARA NO. 13/KPPU-I/2019 DAN 10/KPPU/-1/2016) - Princessa Deanera; Siti Anisah (Al-Adl : Jurnal Hukum, 2022)
The research entitled "Analysis of Relevant Market in KPPU Decisions (Study on Case Decisions No. 13 / KPPU-I / 2019 and 10 / KPPU / -1 / 2016)" raises two problem formulations, namely: first, how is the determination of the relevant market in Case Decisions. No. 10 / KPPU-I / 2016 and 13 / KPPU-I / 2019? Second, is the determination of the relevant market in Case No. 10 / KPPU-I / 2016 and 13 / KPPU-I / 2019? This research is a normative or doctrinal legal research, which describes, explains, and analyzes legal materials that refer to laws and regulations and KPPU's decisions relating to the determination of the relevant market. Analysis in legal materials in this study uses a qualitative descriptive approach, which is carried out by collecting legal materials, qualifying them, connecting theories related to research problems, drawing conclusions to determine the results and recommendations. The results of this study indicate, in Case No. 10 / KPPU-I / 2016, KPPU does not consider indicators (price, characteristics, and function) of the relevant market and geography. Meanwhile, in the case No. 13 / KPPU-I / 2019, KPPU makes considerations based on indicator indicators (price, characteristics, and functions). Thus, it appears that the two KPPU decisions are not in accordance with the provisions of KPPU Regulation No. 3 of 2009.